The Swiss franc's honeymoon - Alexandra Janssen; Rahel Studer (University of Zurich, Department of Economics, 2017)
Starting from the stylized fact that the Swiss franc is a safe haven currency, this paper focuses on the determinants of the Swiss franc during the lower bound regime from September 2011 to January 2015. We describe the Swiss franc as a function of global market risk fundamentals and find that the macroeconomic model outlined by Krugman (1991) describes the EUR/CHF exchange rate well during this particular time. We show that, as predicted by Krugman's model, the sole expectation that the Swiss National Bank would prevent the Swiss franc from appreciating beyond 1.20 to the euro muted the sensitivity of EUR/CHF to global market risk. An important assumption for the model prediction to hold is that the central bank's commitment to the exchange rate target is credible. We thus use EUR/CHF option prices together with the global market risk fundamental to assess the credibility of the lower bound. We find that the only true credibility issue was in November 2014. After November 2014 the Swiss National Bank could convince markets anew from its target-zone policy and suspend the lower bound unexpectedly a few weeks later.
Keywords: E52; E58; F31; G01; 330; Exchange rate target zone; safe haven currency; volatility smile